Coalitionary intra-group aggression by wild female bonobos - Pashchevskaya, Sonya; Fruth, Barbara; Kjærland, Sofia Lunde; Berton, Leonardo; Vigilant, Linda; Hohmann, Gottfried (My University, 2025)
In humans and non-human primates, male aggression and physical violence are common strategies in the struggle over power and are efficient in exerting control over individuals and groups. In contrast, our close relative, the bonobo (Pan paniscus) is often described as an exceptionally peaceful primate due to the lack of lethal aggression or infanticide and the tendency for individuals to reconcile after conflicts. Nonetheless, rates of male aggression are high1, but, atypically for primates, bonobo females are observed to confront males without support from others. Despite female exogamy, forming coalitions of unrelated females in response to male aggression appears to be a common strategy, mostly involving charging or chasing and, in some cases, escalating to physical attacks2,3,4. Here, we report on a violent coalitionary attack by resident females against an adult male in a well-studied group of wild bonobos habituated to observation, detailing participants’ violent actions and the victim’s responses. The assault involved a fraction of the group, while almost everybody was present, and bystanders, including some close maternal kin, did not support the victim. Our observations detail a rare behavior that is not easy to reconcile with the assumed peaceful nature of bonobo society, but which contributes to evolutionary models of aggression5.
Keywords: 570